2021
DOI: 10.3390/jcm10061302
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin for Percutaneous Sclerotherapy of Venous and Lymphatic Malformations: A Retrospective Study of Safety, Efficacy and Mid-Term Outcomes in 26 Patients

Abstract: Percutaneous sclerotherapy is used to treat venous and lymphatic vascular malformations, which can cause significant discomfort and/or disfigurement. The purpose of this study is to describe the bleomycin sclerotherapy technique and to evaluate its clinical and radiological efficacy and safety. We retrospectively identified consecutive patients with venous malformations (VMs) and lymphatic malformations (LMs) who underwent bleomycin sclerotherapy in 2011–2020 at our institution. We collected the clinical and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
1
15
3
Order By: Relevance
“…A similar picture is drawn by Gorman et al with an average volume of 156ml and a range of 3-1703ml [7]. Even larger VMs (> 4000ml) were used in the study by Nevesny et al [12].…”
Section: Discussionmentioning
confidence: 68%
“…A similar picture is drawn by Gorman et al with an average volume of 156ml and a range of 3-1703ml [7]. Even larger VMs (> 4000ml) were used in the study by Nevesny et al [12].…”
Section: Discussionmentioning
confidence: 68%
“…Recent literature has demonstrated that sclerotherapy may be ineffective for patients with distensible, venous-dominant moderate-flow OVLM due to frequent recurrence 4. OVLM recurrence rates as high as 23% postsclerotherapy and 58% postsurgical resection have been reported 5,6…”
Section: Discussionmentioning
confidence: 99%
“…Because much of the volume of low-ow VMs consists of stagnant intraluminal uid, percutaneous sclerotherapy, which can be done with liquid (ethanol, sodium tetradecyl sulfate (STS), bleomycin), semiliquid (NBCA glue, onyx) or solids (particles, absorbable gelatin powder), is widely advocated as the treatment of choice [8,12,[15][16][17][18][19][20]. Surgery is reserved for select cases not amenable to sclerotherapy, VMs that are large and dis guring or for whom embolization alone is insu cient.…”
Section: Discussionmentioning
confidence: 99%